Emergence of Haemophilus influenzae Strains in the Nasopharynx of Children with Tuberculosis - Martynova, Alina V.; Balabanova, Larisa A.; Pruschinskyi, Alexei (Pulmonary Medicine, 2011)
Being rigorously studied, epidemiology aspects of Haemophilus influenzae carriage are still remaining unclear. Especially it concerns such a group as children with low immune status and also such groupas children with tuberculosis infection. We examined nasopharyngeal tract of children with tuberculosisinfection in remission and checked how often these children are carriers of Haemophilus influenzae strains. Also we gained microbiology characteristics of the isolates and defined the clinical significance ofH. influenzae carriage in development of opportunistic infections in children with the tuberculosis infection.